COUNTRY BRIEFING PAPER-PORTUGAL. Posting of workers - Luísa Veloso; Marques, Joana; Sales Oliveira, Catarina (ISA - Information Sharing Agreements, 2020)
The Country briefing paper provides contextual information on trends and debate about posting in a nutshell.